The Impact of the Teaching Competence of Science Teachers and Their Attitudes Towards the Role of the Teacher Preparation Program for the Basic Stage in Khartoum - Yousif, Taghreed Mohamed (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to reflect the reality of the science teacher preparation program for the basic stage in Khartoum from the teachers' point of view. The researcher used the analytical descriptive approach in the Sudanese public schools. A random sample of 334 male and female teachers participated in the study. The data collection tools included a questionnaire for teachers. To analyze the data, the Statistical Program for Social Sciences (SPSS) was used to test the means, standard deviation, and percentage, as well as the relationship between demographic information and the role of the teacher preparation program for the primary stage. Accordingly, the study revealed several findings. The most important of them; there is no statistically significant relationship at the level of significance (α = 0.05) between age, academic qualification, and experience on the role of the teacher preparation program for the basic stage in raising teaching efficiency in Khartoum, where the statistical function for the age variable was 0.401, and the statistical function for the qualification variable was 0.401. Scientific 0.846, and experience 0.791. As for the gender variable only, the study showed that there is a statistically significant relationship at the significance level (α = 0.05), where the statistical function was 0.000. Also, from the foregoing, it becomes clear that the training available to teachers is not sufficient for the needs of teachers, just as planning is not characterized by the required flexibility and creativity, and the objectives of the training program are not measurable, and as it was found that the training content is not characterized by a balance between academic and professional preparation, and there are also problems and issues facing in-service teacher training. In light of these results, some recommendations were reached, the most important of which are; link training courses to teachers' real needs, training should be planned by experts, learning objectives should be built in a procedural manner, and should be measurable, evaluation of training courses should include both theoretical and practical aspects.
Keywords: Teaching Competence; Science Teachers; Science Teachers' Attitudes; Teacher Preparation Program for the Basic Stage; Khartoum